2007
DOI: 10.1007/s00125-007-0731-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological localisation of sulfonylurea receptor 1 in endocrine cells of human, mouse and rat pancreas

Abstract: Aims/hypothesis Sulfonylurea receptor 1 (SUR1) is the regulatory subunit of ATP-sensitive K channels in beta cells. Morphological methods (immunohistochemistry and sulfonylurea binding) were used to establish the cellular and subcellular location of SUR1 in human and rodent islets. Results In the human, mouse and rat pancreas, all endocrine cells of the islets were immunolabelled with an anti-SUR1 antibody, whereas tissues containing SUR2 were consistently negative, as were those from Sur1 (also known as Abcc8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
0
28
0
1
Order By: Relevance
“…It has been suggested that Cl influx into granules occurs through ClC-3 channels regulated by a sulfonylurea receptor-like protein (16). Although SUR1 is present in the insulin granule membrane (44,45), it is not involved in the acidification by glucose since the phenomenon was unaltered in islets from Sur1 knock-out mice (Fig. 5I) (46) or stimulation of the phospholipase C-protein kinase C pathway by activating muscarinic receptors with 10 M acetylcholine (47) had no effect on granular pH in low glucose and did not affect the acidification by 15 mM glucose (data not shown).…”
Section: Characteristics Of the Ph-sensitive Probe Lysosensor Dnd-160-mentioning
confidence: 99%
“…It has been suggested that Cl influx into granules occurs through ClC-3 channels regulated by a sulfonylurea receptor-like protein (16). Although SUR1 is present in the insulin granule membrane (44,45), it is not involved in the acidification by glucose since the phenomenon was unaltered in islets from Sur1 knock-out mice (Fig. 5I) (46) or stimulation of the phospholipase C-protein kinase C pathway by activating muscarinic receptors with 10 M acetylcholine (47) had no effect on granular pH in low glucose and did not affect the acidification by 15 mM glucose (data not shown).…”
Section: Characteristics Of the Ph-sensitive Probe Lysosensor Dnd-160-mentioning
confidence: 99%
“…Shyng, University of California, USA), which was detected by the EnVision peroxidase complex (1 h; Dako, Carpintera, USA) and by 3,3′-diaminobenzidine (DAB; brown deposit; Guiot et al 2007). For electron microscopy, after the removal of Epon with sodium metaperiodate (Merck, Darmstadt, Germany) and pretreatment with 0.1% trypsin/0.1% CaCl 2 (Sigma-Aldrich, Steinheim, Germany) in phosphate-buffered saline (PBS) for 20 min at 37°C, semi-thin (1 µm thick) or ultra-thin (75 nm) pancreas sections were incubated overnight at 4°C with rabbit anti-Kir6.2 (1/20) or with goat anti-calreticulin (1/100; Santa Cruz, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%
“…The results were expressed as the number of particles per micrometer L-RER length or per insulin granule (modified from Guiot et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…For histology and immunochemistry, sections were either stained with haematoxylin-eosin or immunolabelled for insulin, pro-insulin and SUR1 peptides as described by Guiot et al (2007).…”
Section: Immunohistochemistry and Morphometrymentioning
confidence: 99%
“…They play a key role in the control of insulin secretion by linking the electrical membrane activity to the cellular metabolic rate (Dunne et al 1997;Ashcroft and Gribble 1998;Henquin 2000). The presence of functional K-ATP channels (Göpel et al 2000;Gromada et al 2004;MacDonald et al 2007) or their molecular subunits (Bokvist et al 1999;Guiot et al 2007) has also been found in other islet cells secreting glucagon (α) and somatostatin (δ).…”
Section: Introductionmentioning
confidence: 98%